Functional ferritin-polymer complex for electrical applications - Tanjaya, Michelle Cordelia (Nanyang Technological University, 2024)
The iron storage capability of the nanocage protein ferritin provides charge transfer capabilities that has been successfully applied for enhancement or modulation of electrical properties on components such as memristors and bilayer graphene. Building upon this premise, the guided assembly of ferritin molecules into a higher order structure by employing hydrogels presents a potential for a novel model suitable for electrical applications. This method of assembly can be achieved through effectively immobilizing the ferritin molecules in position within the interconnected hydrogel networks. To fulfil this, a naturally derived polymer, chitosan, is combined with the ferritin from the hyperthermophilic archaea (AfFtn-AA). Gelation is initiated through a freeze-melting-neutralization method, inducing a salting-out effect in chitosan that facilitates self-crosslinking, leading to the formation of gels. The constructed ferritin-chitosan gel exhibits near-uniform particle sizes and pores when observed under the Scanning Electron Microscope. Furthermore, cyclic voltammetry (CV) analysis reveals a reduction in peak potential difference (ΔEp), suggesting improved conductivity following modification of chitosan gels with ferritin nanocages. Overall, the construction of a ferritin-chitosan hydrogel complex presents a promising avenue for its application in electrical systems.